Current Sustainable Development: Urban Region for a Livable City - Dzulkipli, Sarah Nadira; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
The construction industry has a substantial impact on the worldwide environment. Therefore, this industry has a disproportionate effect on our economy, culture, and environment. While sustainable construction has gained increased attention in recent years, construction professionals are unaware of its full potential. Having stated that, this research will examine the long-term viability of construction projects in Kuala Lumpur, Malaysia in accordance with the principles of sustainable state development. The objectives of the research are to identify the impact of development in the absence of sustainable development and to investigate the current contribution factors of poor implementation of sustainable development city in Malaysia. Following, one form of analysis, the quantitative method, is employed to achieve the study’s objectives by distributing a survey form questionnaire to G7 construction firms in Kuala Lumpur, Malaysia. From a total population of 2,615 contractors, 313 contractors were selected as responders for this research, with a response rate of 32 percent. Consequently, Statistical Package for the Social Sciences (SPSS) software will be used to examine research data gathered via the distribution of questionnaires. A descriptive statistical analysis, including frequency distribution and mean score, is necessary for determining the impacts, current contribution factors and the improvements in order towards livable city in Kuala Lumpur. The research study was conducted within the Kuala Lumpur construction zone. The projected consequence of this study is that the absence of sustainable development will have negative impacts and factors not only on the environment, but also on the economy and society. Nevertheless, these impacts and factors can be effectively opposed by enhancing sustainable development in order to create a livable city in Kuala Lumpur, Malaysia. The impacts and factors must be taken rigidly, efficiently, and effectively in order to mitigate them. This research is expected to ensure environmental sustainability, economic development, and social wellbeing in relation to sustainable development in the construction industry.